Обзор и классификация протоколов маршрутизации в беспроводных сетях - Евдокименко, М. А.; Ахмед Хассан Абед (ХНУРЭ, 2011)
One of the promising areas of wireless networks is a research and development used in these algorithms and routing protocols. After analyzing the existing solutions have been put forward demands for improvements to existing and developing new routing protocols for wireless networks.
Keywords: мультисервисные сети; мультипротокольная коммутация